(untitled) (Orthodontic Journal of Nepal, 2018)
Objective: To compare the mean changes in dentoskeletal parameters in Class II patients treated by Twin Block versus Herbst appliance. Materials & Method: The study was conducted at the Orthodontic Department of Children’s Hospital and Institute of Child Health and de’Montmorency College of Dentistry, Lahore. The study involved 50 patients those were randomized in equal numbers according to lottery method to either Group-1 (Twin block) or Group-2 (Herbst). Mean changes in SNA, SNB and IMPA at the end of treatment was calculated by subtracting Pretreatment measurements (T1) from post treatment measurements (T2). Student t–test was used to compare the mean changes in dentoskeletal parameters in both groups. Result: The comparison showed that the mean difference recorded in SNA values was -1.06±0.62 in Group-1 and -1.28±0.61 in Group-2 (p-Value 0.07), SNB was 2.14±0.70 in Group-1 and 1.22±0.55 in Group-2, (p-Value 0.001) while IMPA was 1.58±0.64 in Group-1 and 4.8±1.31 in Group-2 (p-Value 0.001). Conclusion: There was a significant difference between mean changes in dentoskeletal parameters in Class II patients treated by twin block when compared to Herbst appliance.